A commercialization project for Gamitana in Lima, Peru - Curonisy Velarde, Yanitza (2018)
The gamitana is a fish native to the Amazon and Orinoco River basin, with a growing demand in Peru, especially in supermarkets and restaurants specializing in traditional Amazonian jungle cuisine, with an estimated demand of approximately 600 kilos per week, due to the product’s quality, homogeneous organoleptic properties, strict quality control, certifications and product auditing.The objectives of this study are to redefine the strategy and redesign the supply chain of Puñizas SAC, a familyrun company located in Junín dedicated to gamitana production and distribution to supermarkets and Amazonian restaurants in Lima, in order to add value to clients focused on product (gamitana) flow.